THE DEVELOPMENT AND PRACTICE OF STRATEGIC ENVIRONMENTAL ASSESSMENT (SEA) IN KENYA - Mutui, Frida Nyiva; Cun-kuan, Bao; Onyango, Vincent; Muhandiki, Victor; Mwaura, Francis (European Scientific Journal, ESJ, 2013)
This paper provides an analytical description of the emerging Kenyan Strategic Environmental assessment (SEA) system as an example from Sub-Sahara Africa, focusing on its form, purposes and implementation. Three features are of particular interest: first, the extent to which the Kenyan SEA operates within a formally recognized regulatory framework of protected rights; second, the policies and institutions which act as agencies of the SEA system; and third, the procedural and substantive requirements of the Kenyan SEA process. It is concluded that the current political and decision-making context, following the new constitution, has created a well-protected and enforceable regulatory system for SEA. However, the successful development of SEA in Kenya will likely depend on 1) internalization and subsequent innovative application of the existing framework; 2) the effective integration of SEA at both the national and regional levels; 3) the level of commitment SEA will get from the emerging political and decision-making cultures; and 4) continuous use of empirical and evaluatory feedback to evolve the system.